Three-Dimensional Modeling of Spatial Reinforcement of Soil Nails in a Field Slope under Surcharge Loads - Yuan-de Zhou; Kai Xu; Xinwei Tang; Leslie George Tham (Journal of Applied Mathematics)
Soil nailing has been one of the most popular techniques for improving the stability of slopes, in which rows of nails and a structural grillage system connecting nail heads are commonly applied. In order to examine the spatial-reinforcement effect of soil nails in slopes, a three-dimensional (3D) numerical model has been developed and used to back-analyze a field test slope under surcharge loading. Incremental elastoplastic analyses have been performed to study the internal deformation within the slope and the development of nail forces during the application of top surcharge loads. Different treatments of the grillage constraints at nail heads have been studied. It is shown that the numerical predictions compare favorably with the field test measurements. Both the numerical and the field test results suggest that soil nails are capable of increasing the overall stability of a loose fill slope for the loading conditions considered in this study. The axial force mobilization in the two rows of soil nails presents a strong dependence on the relative distance with the central section. With the surcharge loads increased near the bearing capacity of the slope, a grillage system connecting all the nail heads can affect the stabilizing mechanism to a notable extent.